Development of recombinant West Nile virus expressing mCherry reporter protein - Kobayashi, Shintaro; Fukuda, Yukine; Yoshii, Kentaro; Thammahakin, Passawat; Maezono, Keisuke; Eyer, Luděk; Růžek, Daniel; Kariwa, Hiroaki (Journal of virological methods, 2023)
West Nile virus (WNV) is transmitted to humans and animals by a mosquito and enters the central nervous system, leading to lethal encephalitis. Reporter viruses expressing fluorescent proteins enable detection of infected cells in vitro and in vivo, facilitating evaluation of the dynamics of viral infection, and the development of diagnostic or therapeutic methods. In this study, we developed a method for production of a recombinant replication-competent WNV expressing mCherry fluorescent protein. The expression of mCherry was observed in viral antigen-positive cells in vitro and in vivo, but the growth of the reporter WNV was reduced as compared to the parental WNV. The expression of mCherry was stable during 5 passages in reporter WNV-infected culture cells. Neurological symptoms were observed in mice inoculated intracranially with the reporter WNV. The reporter WNV expressing mCherry will facilitate research into WNV replication in mouse brains. •A reporter WNV with mCherry expression (mCh-WNV) was produced.•mCherry expression was observed in viral antigen-positive cells in vitro and in vivo.•Neurological symptoms were induced by intracranial inoculation of mCh-WNV.